Triple Endobutton with Coracoacromial Ligament Transfer: A Modified Technique for Fixation of Acromioclavicular Joint Dislocation - Vikas Kesari; Jatin Prakash; Jyoti Garg; Divesh Jalan; Karan Maggo; Naval Bhatia (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: The study explores a novel technique for the fixation of acromioclavicular joint (ACJ) dislocation utilizing triple Endobutton and coracoacromial ligament (CAL) transfer. ACJ dislocations are common injuries that can lead to significant functional impairment and pain. Current treatment options often fall short of providing long-term stability and functional outcomes. Therefore, the development of new techniques is imperative to enhance patient outcomes. Materials and Methods: A prospective analysis was conducted on a cohort of patients with ACJ dislocation who were treated using the triple Endobutton and CAL transfer techniques. In this procedure, the lateral end of the clavicle, the coracoid, and the CAL were exposed. Two tunnels were drilled in the lateral clavicle and one in the coracoid. An Endobutton loaded with No. 2 FiberWire was passed under the coracoid and the medial clavicle tunnel in a retrograde manner. ACJ was then reduced and the No. 2 FiberWire was tied over the Endobutton on the clavicle. CAL was then passed through the lateral clavicle tunnel and tied over the Endobutton. Patients were evaluated based on clinical, radiological, and patient-reported outcomes. Results: In this study, 38 patients underwent ACJ dislocation repair using the triple Endobutton and CAL transfer technique. The patients’ ages ranged from 22 to 48 years, with a mean age of 39.4 years. The majority of patients was males (24) and had right-sided injuries (21). Dislocations were predominantly grade V (16 cases). Postoperative outcomes showed significant improvements in pain levels, functional scores, and joint alignment. The average Visual Analog Scale score decreased from 6.24 to 0.62, Constant Shoulder score improved from 29.5 to 88.3, and disability of the arm, shoulder, and hand scores decreased from 21.79 to 1.33. Radiographic evaluation demonstrated satisfactory joint alignment with no significant differences between right and left CC distances. No loss of reduction or major complications were observed, although two cases of superficial skin infections were treated successfully. Conclusion: The triple Endobutton and CAL transfer technique represents a satisfactory technique in the fixation of ACJ dislocation.